Efisiensi Rem Utama dan Rem Parkir Kendaraan Mobil Barang Dengan Variasi Tekanan Angin Ban - Azalia, Noni Gytha; Siti Shofiah; Ambarita, Sihar (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
Tire pressure requirements may vary for different vehicles depending on factors such as the brand, load, and tire type. Inadequate tire pressure can result in suboptimal braking performance. This study aims to examine the impact of tire pressure variations on the efficiency of the main brake and parking brake in vehicles. The brake tester was utilized to conduct experiments on pickup goods vehicles with a GVWR less than 3,500 kg. The findings reveal that tire pressure has a significant influence on the efficiency of the main brake and parking brake. Higher tire pressure corresponds to lower efficiency values for both brakes, while lower tire pressure yields higher efficiency values. It is crucial to raise awareness among vehicle owners about the importance of maintaining proper tire pressure as it directly impacts braking performance and overall vehicle safety.